First report of the house fly larvae, Musca domestica (Linnaeus) (Diptera: Muscidae) associated with the monkey carcass in Malaysia. - Chen, C.D.; Lee, H.L.; Nazni, W.A.; Ramli, R.; Jeffery, J.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2010)
A study on insect succession of monkey carcass in a forested area in Ulu Gombak, Selangor, Malaysia was conducted from 9 May to 18 June 2007. The third instar of the housefly, Musca domestica (Linnaeus) (Diptera: Muscidae) were only found on dry stage of a decomposed (Day-33) monkey carcass (Macaca fascicularis Raffles). This observation revealed that M. domestica maggots were found together with other muscid fly maggots, Hydrotaea (=Ophyra) spinigera (Stein) (Diptera: Muscidae) on dry stage of a carcass. However, the role of M. domestica on forensic entomological study remains unknown. This study recorded the first finding of M. domestica maggots on primate carcass in Malaysia.